2015
DOI: 10.1007/s00371-015-1134-7
|View full text |Cite
|
Sign up to set email alerts
|

Real-time simulation techniques for augmented learning in science and engineering

Abstract: In this paper we present the basics of a novel methodology for the development of simulation-based and augmented learning tools in the context of applied science and engineering. It is based on the extensive use of model order reduction, and particularly, of the so-called Proper Generalized Decomposition (PGD) method. This method provides a sort of meta-modeling tool without the need for prior computer experiments that allows the user to obtain real-time response in the solution of complex engineering or physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In any case, PGD methods provide a very appealing way of developing surgical simulators able to run is very simple platforms (typically, in a standard laptop), and even on smartphones or tablets [33]. Notably, it enables the possibility of developing surgical simulators including state of the art (usually, hyperelastic) constitutive laws and momentum and energy conserving, unconditionally stable, dynamical integrators.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, PGD methods provide a very appealing way of developing surgical simulators able to run is very simple platforms (typically, in a standard laptop), and even on smartphones or tablets [33]. Notably, it enables the possibility of developing surgical simulators including state of the art (usually, hyperelastic) constitutive laws and momentum and energy conserving, unconditionally stable, dynamical integrators.…”
Section: Discussionmentioning
confidence: 99%
“…In the StaticAR project, for example, augmented reality is employed to visualize member forces in wooden scale models [25]. Model order reduction techniques are used to speed up complex calculations and to provide results in real‐time for a wide range of engineering applications [38]. These tools are of great interest for conveying intuitive structural insight at the bachelor level, as they are conceived as black‐box software tools that allow users to perform basic analysis with little prior knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of foreign studies showed the relevance of the issues related to the implementation of etextbooks in the educational process. The following foreign researchers studied the specifics of using etextbooks: Baker-Evelet and Stone (2015), Bossaller and Kammer (2014), Johnston et al (2015), Quesada et al (2015), Van Horn, Russell and Schuh (2016), Kachler (2017), Gresty and Edwards-Jones (2012), Brew and Boud (1995) and others. Most of their works focus on determining the effectiveness of using etextbooks using surveys and engaging expert groups.…”
Section: Introductionmentioning
confidence: 99%